Preparation of efficient and reusable lanthanum and iron co-modified soda residue for selective phosphate removal from domestic sewage - Huiteng Wang; Hui Luo; Rubin Han; Wenbo Wu; Jing Yang; Teng Qin; Limin Chen; Meng Liu; Bao-Jie He; Zhaoqian Jing (Scientific Reports)
Abstract The selection of suitable raw materials as adsorbents is a key factor in effectively removing phosphorus from water. As an industrial by-product, soda residue exhibits high porosity and surface area, which can effectively adsorb pollutants. Magnetic lanthanum-iron soda residue (La-Fe-CSR) was synthesized using the co-precipitation method, and its characterization and mechanism for removing phosphate were thoroughly investigated. La-Fe-CSR exhibited good adsorption performance under acidic conditions (3 < pH < 7). A high concentration of HCO3 − (100 mg/L) reduced the adsorption performance of La-Fe-CSR by 8.3% ± 2.5%, whereas the presence of other coexisting ions had a smaller impact. The adsorption of phosphate by La-Fe-CSR was controlled by chemisorption and reached saturation after approximately 120 min. The phosphate adsorption by La-Fe-CSR was significantly higher than that of soda residue (43.65 ± 3.39 mg/g), reaching 74.87 ± 2.46 mg/g. Ligand exchange and inner-sphere complexation constituted the primary mechanisms through which L-Fe-CSR removed phosphate. After 5 consecutive cycles, La-Fe-CSR maintained a phosphate removal efficiency of 74.5 ± 1.6%. It demonstrated good performance in removing total phosphorus from real domestic sewage, with a removal rate of 94.9 ± 0.5%. These research findings demonstrated that La-Fe-CSR held significant promise as a highly effective phosphate adsorbent in practical applications.